Exploring Social-Emotional Learning (SEL) Practices in Junior High Schools: A Case Study of Teachers’ Perspectives and Experience - Utami, Ferisa Prasetyaning; Hananto, Ipung; Sari, Permata (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2025)
The learning process that incorporates social and emotional aspects is expected not only to transfer knowledge but also to foster morals and ethics. The aim of this study is to understand the experiences of implementing social-emotional learning (SEL) in junior high schools by teachers in developing students’ social-emotional competencies, particularly the types of approaches used during instruction. This research is a qualitative case study. The respondents were 9 teachers and 3 principals, selected through purposive sampling. The primary research instrument was the researcher, who collected data through in-depth interviews, observations, and documentation. Data analysis followed three stages: data reduction, data display, and conclusion drawing. The transcribed data were analyzed using NVivo 12 to support data visualization. The results indicate that the most frequently used approach to SEL implementation was teacher instructional practice, specifically teachers’ emotional awareness strategies. This means that before teaching SEL to students, teachers strive to cultivate their own emotional regulation and appropriate social interaction skills.